2013
DOI: 10.1039/c3cp52444b
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of effective pairwise potentials for UO2n+, NpO2n+, PuO2n+, and AmO2n+ (n = 1, 2) ions with water

Abstract: Intra- and intermolecular force field parameters for the interaction of actinyl ions (AnO2(n+), where, An = U, Np, Pu, Am and n = 1, 2) with water have been developed using quantum mechanical calculations. Water was modeled with the extended simple point charge potential (SPC/E). The resulting force field consists of a simple form in which intermolecular interactions are modeled with pairwise Lennard-Jones functions plus partial charge terms. Intramolecular bond stretching and angle bending are treated with ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 84 publications
10
63
0
Order By: Relevance
“…All simulations were performed by using NAMD 2.10 program . The force field parameters used to describe uranyl were taken from a recent work . The proposed intramolecular parameters performed well for the description of uranyl in water system.…”
Section: Methodsmentioning
confidence: 99%
“…All simulations were performed by using NAMD 2.10 program . The force field parameters used to describe uranyl were taken from a recent work . The proposed intramolecular parameters performed well for the description of uranyl in water system.…”
Section: Methodsmentioning
confidence: 99%
“…Wipff and Guilbaud 33,79 and Keristi and Liu 34 from MD using empirical interaction potentials, and Siboulet et al 21 from QM computations found one hydrogen atom at around 1.8 Å from the uranyl oxygen forming typical hydrogen bonding. On the contrary, Roos et al 35 and Maginn et al 37,38 with classical MD using ab initio potentials; Bühl et al, 77 Frick et al, 42 and Nichols et al 41 using ab initio MD did not find preferential HB formation; furthermore, a low density number region is obtained, which led them to propose a rather hydrophobic behaviour in the uranyl axial region.…”
Section: B Hydration Structure Of Uranyl In Aqueous Solutionmentioning
confidence: 98%
“…In this work the importance of introducing charge transfer terms to describe the hydrate of a doubly charged ion in solution, such as uranyl, was shown. Maginn et al 37,38 considered the importance of polarization and other many-body effects in the binding of water molecules to the cation. They developed another firstprinciples force field for uranyl by parameterizing the interaction energies of the cation in the presence of four hydration water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…All the actinyls of this study have open-shell electron configurations except uranyl. We will evaluate the goodness of the DFT mean field treatment of static electronic correlation effects to provide an accurate enough EXAFS spectrum prediction for open-shell actinyls, since DFT has shown the ability of our model to reproduce many other experimental properties [23,34,35]. To get insight into this question and check the EXAFS sensitivity to minute structural changes, multi-reference NEVPT2 [36][37][38] computations have been performed to build a [NpO 2 ] + −H 2 O interaction potential based on this quantum-mechanical level.…”
Section: Introductionmentioning
confidence: 99%